Mobile Apps and Sustainable Development of Voluntary Organizations - et. al., Dr. Ashwini Patil, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
ICT support in voluntary organizations is an interesting emergent field of research. The voluntary organizations are aware about the use of technology in their activities but the complexity of technologies, lack of technological knowledge, lack of funds and lack of standards are big obstacles. There is a need to transform the operation and structure of these organizations, as the roles and functions of voluntary organizations have significantly expanded in recent years. The current research objective is to investigate the current scenario of the implementation of ICT by the voluntary organizations. The objectives of the study were to study the usage of ICT, impact of ICT and satisfaction level of ICT in voluntary organizations, also to study the issues and challenges they are facing. The study was conducted in and around Pune. Questionnaires were managed to various voluntary organizations and the results of this are analyzed. Based on the investigation, recommendations are made and mobile application using open source technologies is suggested.